Explore the use of cobalt chloride (II) to determine the moisture content of transformer oil - L. I. Musaeva; A. P. Kulikova; V. K. Kozlov; L. G. Gafiyatullin; O. A. Turanova; A. N. Turanov (Известия высших учебных заведений: Проблемы энергетики)
In presented work the methods of determining the moisture content in transformer oil are listed, their advantages and disadvantages are discussed, the idea of a new method is proposed, it based on the color change of cobalt chloride (II) hydrate due to the dependence of the number of water molecules.